Health Service Use and Treatment Choices for Pediatric Eosinophilic Esophagitis: Findings From a Cross-Sectional Survey of Australian Carers - Hannan, Nicole; Steel, Amie; McMillan, Sara S.; Tiralongo, Evelin (Frontiers in Pediatrics, 2020)
Objectives: Eosinophilic esophagitis (EoE) incidence and prevalence is increasing and healthcare utilization amongst children with EoE is high. This study provides novel insights into the health services and treatments, including complementary medicines (CMs), used by carers to manage their children’s EoE, as well as carers’ beliefs and attitudes towards these treatments. Methods: A national cross-sectional online survey was conducted in Australia between September 2018 and February 2019. The survey included questions about health service and treatment utilization; health insurance and government supports; Health Related Quality of Life of children with EoE and their carers; views and attitudes towards CM use; and perceived efficacy of treatment. Results: The survey was completed by 181 carers (96.6% mother) of an EoE child. Most children (91.2%, n=165) had seen a medical doctor for their EoE and almost half had consulted with a CM practitioner (40.3%, n=73). Pharmaceuticals (n=156, 86.2%) were the most commonly used treatment option, followed by dietary changes (n=142, 78.5%), CM products (n=109, 60.2%), and CM therapies (n=42, 23.2%). Most children received care from numerous practitioners on multiple occasions, indicating a substantial financial and treatment related burden. Conclusions: A variety of practitioners are involved in the care of children with EoE and a high rate of CM use warrants further attention to ensure appropriate treatment is provided. Carer involvement and guidance, combined with individual practitioner expertise, referrals and collaboration between providers is essential to successfully navigate this complex disease and provide adequate care for these patients.